2019
DOI: 10.4995/wrs.2019.8923
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic diversity and conservation priorities of Egyptian rabbit breeds

Abstract: <p>The limited rabbit resources in Egypt are threatened by the danger of extinction, whereas genetic diversity studies of native breeds could play a vital role in conservation and improvement of these breeds. In this study, 3 native rabbit breeds: Gabali (G), Baladi Red (BR) and Baladi Black (BB), in addition to New Zealand White (NZW), were genotyped using 12 microsatellite markers. All the typed microsatellites were polymorphic by average number of alleles 5.25 per locus. Observed and expected heterozy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
(27 reference statements)
2
4
0
Order By: Relevance
“…This may be due to differences in genetic make-up of the two lines. These results are in agreement with the same trend obtained by Afifi et al (2000); Iraqi (2003) and Badr et al (2019).…”
Section: Live Body Weight Effect Of Breedsupporting
confidence: 94%
“…This may be due to differences in genetic make-up of the two lines. These results are in agreement with the same trend obtained by Afifi et al (2000); Iraqi (2003) and Badr et al (2019).…”
Section: Live Body Weight Effect Of Breedsupporting
confidence: 94%
“…BB breed was genetically diverged from the NZW breed, which was in agreement with Grimal et al (2012), who found that four Egyptian breeds were structurally separated from the Spanish NZW line. Moreover, this result was consistent with Badr et al (2019), who reported that G, BR and BB breeds were more distinct from the NZW breed, using microsatellite markers. Galal et al (2013) stated that the genetic variation in domestic breeders allows the evolution of new features for environmental changes or adaptation to diseases.…”
Section: Discussionsupporting
confidence: 91%
“…Mohamed and Abdelfattah (2018) used RAPD and SRAP markers to assess the genetic diversity and similarity among six rabbit breeds: G, Bouscat, Chinchilla, Flemish, Cal and NZW. Badr et al (2019) applied 12 microsatellite loci to investigate the genetic diversity The results of the partial sequence of 16S rRNA showed that A+T contents of all understudying rabbit breeds tend to be higher than C+G contents (Table 2). The 16S rRNA sequences comprised 569 nucleotides sites of which 547 sites (96%) are conserved (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the calculated genetic similarity, Baladi Black breed display high genetic variation from the New Zealand White breed, this was concordant with Grimal et al 33 who observed structurally separation between four Egyptian breeds and the Spanish NZW line. In the same context Badr et al 34 applied microsatellite markers in four rabbit breeds and noticed that the New Zealand White breed was more distinctly from Gabali, Baladi Red, and Baladi Black breeds.…”
Section: Discussionmentioning
confidence: 99%